2014
DOI: 10.1007/s11695-014-1430-8
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery and Liver Transplantation: a Systematic Review a New Frontier for Bariatric Surgery

Abstract: This study aims to conduct a systematic review on bariatric surgery (BS) for patients in the setting of liver transplantation (LT). A literature review was conducted on the PubMed, Embase, and Cochrane Library databases. Studies in the English language on adults reporting on BS prior to, during, or after LT were included. Eleven studies with 56 patients were retrieved. Two studies reported on BS before, two during, and seven after LT. Sleeve gastrectomy was the most common procedure, followed by Roux-en-Y gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 52 publications
0
65
0
3
Order By: Relevance
“…However, it was also observed that episodes of transient renal failure, longer operation times and greater amounts of intraoperative bleeding and need for transfusion were more common within this group than in the general obese population. In a meta-analysis, Lazzati et al 168 observed a mean excess weight loss of 66% among morbidly obese cirrhotic individuals over a two-year period, which was comparable to the general population.…”
Section: Bariatric Surgery In Cirrhotic Patientsmentioning
confidence: 91%
“…However, it was also observed that episodes of transient renal failure, longer operation times and greater amounts of intraoperative bleeding and need for transfusion were more common within this group than in the general obese population. In a meta-analysis, Lazzati et al 168 observed a mean excess weight loss of 66% among morbidly obese cirrhotic individuals over a two-year period, which was comparable to the general population.…”
Section: Bariatric Surgery In Cirrhotic Patientsmentioning
confidence: 91%
“…In a systematic review, Lazzati et al 21 found a 66% loss of excess weight within two years, comparable to that found in the general population. Vertical sleeve gastrectomy was the procedure conducted the most, and perioperative mortality was similar to that in the general population.…”
Section: Resultsmentioning
confidence: 62%
“…Morbidity is higher than in the general population (reoperation rate of up to 33%) but mortality is similar. 21,22,[28][29][30] conclusion…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations